HUBUNGAN KONSEP DIRI DAN FUNGSI AFEKTIF KELUARGA DENGAN PERGAULAN BEBAS REMAJA - Yosevin, Anggelina; Pradika, Jaka; Fitrian Roshandri, Wien (Literasi Intelektual, 2025)
Background: Self-concept refers to an individual’s perception and understanding of themselves, encompassing what they know and feel about their identity. It represents an essential aspect of personality development, particularly during adolescence, when family support plays a crucial role. One important aspect of family support is the affective function, which involves emotional guidance and preparation of family members to build healthy social relationships and psychological stability. When the affective function of the family is not fulfilled, adolescents are more likely to engage in deviant behaviors such as promiscuity. Promiscuity is a form of social deviation that crosses moral boundaries and may lead to negative outcomes, including free sex. Objective: To determine the relationship between self-concept, family affective function, and adolescent promiscuity at SMA Negeri 1 Simpang Dua, Ketapang Regency. Methods: This quantitative study employed a cross-sectional approach involving 76 respondents. Data were collected through questionnaires and analyzed using the Chi-square test with the SPSS application. Results: The findings showed no significant relationship between self-concept and adolescent promiscuity, with a p-value of 0.195 (>0.05). However, a significant relationship was found between the family’s affective function and adolescent promiscuity, with a p-value of 0.003 (<0.05). Conclusion: The study concludes that while self-concept alone does not significantly influence adolescent promiscuity, the family’s affective function plays a critical role. The weaker the family’s affective function and the more negative the self-concept, the higher the risk of adolescents engaging in promiscuous behavior.